The study of financial performance in Agro Bank (2004 - 2009) / Nurulhayati Adnan - Adnan, Nurulhayati (2011)
This study focused on bank performance but using time series analysis method. The study was conduct to analyze Bank Pertanian Malaysia Berhad (Agro Bank) performance from year 2004 to year 2009. The objectives of the study are to analyze Bank Pertanian profitability performance, to determine their liquidity performance and also to evaluate the bank risk and solvency. This study also indicates on how the bank manages their assets, equity and liability. It is important for the bank managers, depositors and regulators to know the bank performance every year. The method used in this study was financial ratio calculation. There are three grouped of ratio consist of 10 ratios. These ratios were calculated using the bank yearly financial statement except in 2008. The ratios then convert into graph using Microsoft Words and Excel. The result of this study indicates that whether the bank has a good position in generating profits from its assets, equity and deposits from customers. The result also shows that whether the bank was a very risky bank because most of the capital was provide from outsiders. Besides that, the result also finds that is it the bank was a less liquid asset since they were unable to pay their short term obligations.